21. Physical Quality and Organoleptik of Beef Added with Curry Leaf (Murraya koenigii) Infuse - Baida Murliana; Rastina Rastina; Ismail Ismail; Nurliana Nurliana; T. Armansyah TR; Dwinna Aliza (Jurnal Medika Veterinaria, 2018)
The aims of this research were to compare the physical charateristic of meat with or without the addition of curry leaf and to find out the organoleptic of meat added with curry leaf. This research used complex randomized design method. 500 grams beef sample were cut into square-shape at 2x2x2 cm  and divide into 3 groups and  then added a curry leaf infuse with different concentration of 0%, 25%, and 50%. Then, the meat was boiled at 70-80oC for 45 minutes. The parameters observed were pH, water holding capacity, cooking loss, and organoleptic (colour, taste, and aroma). The result showed that the use of curry leaf infuse in various concentration did not have significant effect on pH, water holding capacity, and cooking lost, but significantly effect (P0,05) on organoleptic value. Fresh meat that was added the curry leaf infuse 50% was well-liked for the colour, taste, and aroma  compare to the meat without the addition of curry leaf infuse.